Peran Self-Control Dalam Memoderasi Hubungan Persepsi Kemudahan dan Manfaat Terhadap Perilaku Pembelian Impulsif Pada Pengguna E-Wallet - Rahmawati, Devy; Andhaniwati, Erry (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to test and prove empirically the role of self-control as a moderator in the relationship between perceived convenience and perceived benefits of e-wallet users' impulsive buying behavior. The population used in this study were students majoring in accounting at UPN